Protein Replacement Value of Cassava (Manihot esculenta, Crantz) Leaf Protein Concentrate (CLPC) in Broiler Starter : Effect on Performance, Muscle Growth, Haematology and Serum Metabolites - Fasuyi, A.O.; Aletor, V.A. (International Journal of Poultry Science, 2005)
Cassava (Manihot esculenta, Crantz) leaf protein concentrate (CLPC) was used to replace a known and conventional source of protein in broiler starter diets 2, 3, 4, 5, and 6 at 20, 40, 60, 80 and 100% respectively. The reference diet 1 was one where fish meal was the major source in the diet without CLPC. The inclusion level of CLPC was 1.61, 3.22, 4.82, 6.43 and 8.04 respectively for diets 2 to 6. A batch of 120 starter chicks was randomly assigned in triplicate to these dietary treatments (i.e. chicks/treatment). The final weight and average weight gain of diet 1 (0% FM replacement) was significantly higher than others (P < 0.05) even when the average feed consumption was similar for diets 1, 2, 3 and 4. The feed efficiency (FE) for diets 1 and 2 was also similar (P = 0.05). The nitrogen retention for diets 1, 2 and 4 was similar (P = 0.05). Diets 2, 3 and 4 also had similar values (P = 0.05). The dressed weight of chicks in diets 2 and 6 was similar (P = 0.05) while that of diets 5 and 6 was also similar (P = 0.05). Except for kidney, pancreas and lungs, all other organs measured showed similar values (P = 0.05). The weight of inner chest muscle (supra coracoideus) of birds on diets 1, 2, 3 and 4 were similar (P = 0.05). The weight of outer chest muscle (Pectorialis thoracicus) and thigh muscles (Gastrocnemius) were similar (P = 0.05) with diet 5 (80% FM replacement with CLPC) having the longest inner chest muscle length of 20.7±4.3cmkg-1. Except for red blood cell (RBC) and mean cell volume (MCV), all other parameters measured were similar (P = 0.05). The values of total serum protein, albumin, globulin and albumin/globulin ratio were similar (P = 0.05). Also the values for liver protein, albumin, globulin and liver albumin/globulin ratio were similar (P = 0.05). It was concluded that CLPC as a replacement for FM as a protein source had no deleterious effect up till 60%. However, several parameters investigated strongly support a realistic replacement of 40% FM with CLPC in practical diets. Performance can still be enhanced with supplementation of essential amino acids (EAAs).